Best Value – the English framework for public services improvement - Ćwiklicki, Marek; Wodecka-Hyjek, Angelika (Journal of Public Governance, 2013)
In the article, the English Best Value system is described as one of the more effective frameworks for public services improvement. The authors present the system in the following way: they describe its genesis and its place in the New Public Management concept, discuss the assumptions regarding its application, including the definition of value, the strategies of its increase, and methodological aspects of its implementation. They also compile opinions on the effects of the Best Value regime, and conclude with a statement on the limitations of their research, a discussion of future directions of analysis, and an attempt to evaluate its usability in the Polish context.